KAJIAN KEPUASAN PASIEN AKIBAT SISTEM ANTRIAN PADA PUSKESMAS PAKJO PALEMBANG - Rohmial . (Catholic University Musi Charitas, 2019)
This study was to analyze the queuing system, analyze patient satisfaction and test the effect of the queuing system on patient satisfaction at the Pakjo Public Health Center in Palembang. The sample in this study was 375 respondents. The type of data used is primary data which is carried out through questionnaires. While the analysis technique used is Simple Regression and Community Satisfaction Index. The results showed that the magnitude of the influence of the queuing system on patient satisfaction was 83.8%, and the results of the Community Satisfaction Survei Index value obtained were 3.19 and SKM value was 79.78. Of the 3 indicators, there is only 1 indicator whose value is lower, which is queuing discipline because the service system design has not been maximized such as the number of registration counters and the number of service stages in treatment. This means that the overall service system implemented by the Palembang Pakjo Community Health Center is included in category B so that the service performance can be said to be good.